Segurança da informação no correio eletrônico com base na ISO/IEC 17799 :um estudo de caso em uma instituição superior com foco no treinamento - Cavalcante, Sayonara de Medeiros (2006)
The electronic mail service is one of the most Internet services that grow in the corporate environment. This evolution is bringing several problems for the organizations, especially to information that circulates inside of the corporate net. The lack of correct orientation to the people, about the usage and the security importance of these resources, is leaving breaches and causing misusage and overuse of service, for example. In recent literature, it starts to coming out several ideas, which has helped to rganizations how to plain and how to implement the information security system to the electronic mail in computer environment. However, these ideas are still not placed in practice in many companies, public or private. This dissertation tries to demonstrate the results of a research that has like goal, identify the importance that user training has over the information security policy, through a case study inside of private superior education institute in this state. Besides, this work had by basic orientation the ISO/IEC 17799, which talk about People Security. This study was developed over a proposed model to this research, which looked for offer conditions to guide the institution studied, how to plan better a information security policy to the electronic mail. Also, this research has an exploratory and descreptive nature and your type, qualitative. Firstly, it was applied na questionary to the information technology manager, as better way to get some general data and to deepen the contact which still then, it was being kept through e-mail. Thereupon this first contact, eleven interviews were done with the same manager, beside one interview with twenty-four users, among employees e students. After that to collect and transcript the interviews, were review with the manager all informations given, to correct any mistakes and to update that informations, to then, start the data analyze. The research suggests that the institution has a pro attitude about the information security policy and the electronic mail usage. However, it was clear that answers have their perception about information security under a very inexperient way, derived of a planning lack in relation to training program capable to solve the problem